Impact of a pharmacist driven antimicrobial stewardship program on inpatient antibiotic consumption in a Chinese Tertiary Hospital: a 5-year retrospective study - Qian, Can; Yuan, Ting; Zhang, Fuyong; Gou, Shiyuan; Jiang, Chunmei; Chen, Xuebing; Huang, Ya; Zhao, Xiaolin; Du, You; Li, Chenglong; Han, Yangyun; Su, Huaiyu (Frontiers in Medicine, 2025)
IntroductionAntimicrobial Stewardship programs are crucial for reducing overall antibiotic consumption, but in practice, there are often issues with unclear responsibilities and ambiguous tasks. Pharmacists play a critical role in AMS due to their combined management functions and professional expertise.ObjectiveTo investigate the impact of a Pharmacist-Driven Antimicrobial Stewardship program on the consumption of antibiotics in a hospital.MethodsUnder the support of a hospital top-level design, we implemented a Pharmacist-Driven Antimicrobial Stewardship program led by pharmacists and involving multiple disciplines. The program focused on revising the antibiotic formulary and optimizing key points of antibiotic management, using the inpatient Antibiotic Use Density as the core control indicator. This was conducted through three phases: program initiation, implementation, monitoring and control. Clinical pharmacists ensured the long-term operational quality of the program. We evaluated the impact of the program on relevant indicators of antimicrobial consumption in inpatient.ResultsCompared to the pre-implementation year of 2020, the annual Antibiotic Use Density for inpatients across the hospital decreased by 22.28% in 2024, reaching 36.26 defined daily doses/100 patient days. Additionally, the monthly inpatient Antibiotic Use Density in 2024 was significantly reduced (p < 0.001), along with the antibiotic usage rate (p < 0.05), expenditure on antibiotics per inpatient (p < 0.001), and the proportion of antibiotic expenditure relative to total for inpatients (p < 0.001). The rational use of antimicrobial agents in inpatient wards has been enhanced. Through targeted management, some antibiotics showed trends of increased or decreased usage. The detection rates of Methicillin-Resistant Staphylococcus aureus and Extended-spectrum β-lactamase-producing Escherichia coli did not show a significant decrease.ConclusionThe Pharmacist-Driven Antimicrobial Stewardship program effectively leveraged the managerial roles and professional skills of pharmacists in rational drug use management, resulting in a significant reduction in hospital antibiotic consumption. However, to further validate its effectiveness in reversing bacterial resistance, the program requires longer-term operation and could be considered for regional expansion.